Prevalence of rhinitis among Brazilian schoolchildren: ISAAC phase 3 results - Solé, Dirceu; Camelo-Nunes, Inês Cristina; Wandalsen, Gustavo F.; Rosário Filho, Nelson A.; Naspitz, Charles K.; Cardoso, Maria Socorro; Paes Barreto, Bruno A.; Dantas, Vera; Britto, Murilo; Silva, Almerinda R.; Sarinho, Emanuel; Passos Soares, Francisco J.; et al. (My University, 2007)
Objective: The International Study of Asthma and Allergies in Childhood (ISAAC) is a standardized method that allows international and regional comparisons of asthma and allergic diseases prevalence. The objective of this study was to evaluate the prevalence of rhinitis and related symptoms among 6-7 year-old children (SC) and 13-14 year-old adolescents (AD) from 20 Brazilian cities applying the ISAA C's standardized written questionnaire (WQ). Methods: ISAAC's WQ was applied to 23,422 SC and 58,144 AD living in different regions of Brazil: North (N), Northeast (NE), Middle West (MW), Southeast (SE), and South (S). Results: The prevalence of rhinoconjunctivitis in the last year ranged from 10.3% to 17.4% and from 8.9% to 28.5% among SC and AD, respectively. Considering SC the highest values were observed in SE region. In NE, the prevalence in countryside centres was higher than those along the coast. Among AD, the highest values were observed in N and S regions, mainly in Pará (Belém). The evaluation of populations probably with the same genetic background has shown higher prevalence among those living in urban centres (capital) in comparison to those in the countryside. Conclusions: The prevalence of rhinitis and related symptoms were variable and predominate in Brazilian N and NE centres.
Keywords: Children; Epidemiology; ISAAC; Prevalence; Rhinitis; Rhinoconjunctivitis; adolescent; Brazil; child; clinical trial; human; multicenter study; prevalence; questionnaire; rhinitis; Adolescent; Child; Humans; Questionnaires